Biodegradation of p-nitrophenol by microalgae - Lima, Sofia A. C. (2011)
A study was made on the use of a mixed microalgal consortium to degrade p-nitrophenol. The consortium was obtained from a microbial community in a waste container fed with the remains and by-products of medium culture containing substituted aromatic pollutants (nitrophenols, chlorophenols, fluorobenzene). After selective enrichment with p-nitrophenol (p-NP), followed by an antibiotic treatment, an axenic microalgal consortium was recovered, which was able to degrade p-nitrophenol. At a concentration of 50 mg L−1, total degradation occurred within 5 days. Two species, Chlorella vulgaris var. vulgaris f. minuscula and Coenochloris pyrenoidosa, were isolated from the microalgal consortium. The species were able to accomplish p-NP biodegradation when cultured separately, although Coenochloris pyrenoidosa was more efficient, achieving the same degradation rate as the original axenic microalgal consortium. When Coenochloris pyrenoidosa was associated with Chlorella vulgaris in a 3:1 ratio, complete removal of the nitro-aromatic compound occurred within three days. This is apparently the first report on the degradation of a nitro aromatic compound by microalgae.